The effect of ultrasound-guided high-intensity focused ultrasound treatment for cesarean scar pregnancy on ovarian reserve. (1st January 2021) - Wang, Wenping; Jiang, Jing; Chen, Yan; Li, Chengzhi; Zhou, Honggui; Wang, Zhibiao
Abstract: Objective: The aim of this study was to evaluate changes in anti-Müllerian hormone (AMH) levels after ultrasound-guided high-intensity focused ultrasound (USgHIFU) treatment of cesarean scar pregnancy (CSP). Methods: A retrospective case series study was conducted in the Affiliated Hospital of North Sichuan Medical College. Thirty-two women with cesarean scar pregnancy who met the inclusion criteria were enrolled in the study between January 2018 and December 2019. All patients underwent USgHIFU treatment with or without suction curettage. Intraoperative blood loss in suction curettage and hysteroscopy procedures, time to return of β-human chorionic gonadotropin (β-hCG) to normal levels, and time to recovery of normal menstruation were recorded. AMH levels before and 3 months after HIFU treatment were compared to determine whether USgHIFU treatment affected ovarian reserve. Results: AMH levels before and 3 months after HIFU ablation were 1.87 ± 1.19 ng/ml and 1.90 ± 1.17 ng/ml, respectively. There was no significant difference in AMH levels between the two-time points ( p  > .05). The median volume of intraoperative blood loss was 20 ml, the median time for the serum β-hCG level to return to normal was 35.5 days, and the median time of menstruation recovery was 39 days. Conclusions: USgHIFU treatment for CSP was effective and safe without affecting ovarian reserve.